Prevalence of sleep-disordered breathing in the general population: the HypnoLaus study. Issue 4 (April 2015) - Heinzer, R; Vat, S; Marques-Vidal, P; Marti-Soler, H; Andries, D; Tobback, N; Mooser, V; Preisig, M; Malhotra, A; Waeber, G; Vollenweider, P; Tafti, M; et al.
Summary Background Sleep-disordered breathing is associated with major morbidity and mortality. However, its prevalence has mainly been selectively studied in populations at risk for sleep-disordered breathing or cardiovascular diseases. Taking into account improvements in recording techniques and new criteria used to define respiratory events, we aimed to assess the prevalence of sleep-disordered breathing and associated clinical features in a large population-based sample. Methods Between Sept 1, 2009, and June 30, 2013, we did a population-based study (HypnoLaus) in Lausanne, Switzerland. We invited a cohort of 3043 consecutive participants of the CoLaus/PsyCoLaus study to take part. Polysomnography data from 2121 people were included in the final analysis. 1024 (48%) participants were men, with a median age of 57 years (IQR 49–68, range 40–85) and mean body-mass index (BMI) of 25·6 kg/m2 (SD 4·1). Participants underwent complete polysomnographic recordings at home and had extensive phenotyping for diabetes, hypertension, metabolic syndrome, and depression. The primary outcome was prevalence of sleep-disordered breathing, assessed by the apnoea-hypopnoea index. Findings The median apnoea-hypopnoea index was 6·9 events per h (IQR 2·7–14·1) in women and 14·9 per h (7·2–27·1) in men. The prevalence of moderate-to-severe sleep-disordered breathing (≥15 events per h) was 23·4% (95% CI 20·9–26·0) in women and 49·7% (46·6–52·8) in men. After multivariable adjustment, the upper quartile for the apnoea-hypopnoea index (>20·6 events per h) was associated independently with the presence of hypertension (odds ratio 1·60, 95% CI 1·14–2·26; p=0·0292 for trend across severity quartiles), diabetes (2·00, 1·05–3·99; p=0·0467), metabolic syndrome (2·80, 1·86–4·29; p<0·0001), and depression (1·92, 1·01–3·64; p=0·0292). Interpretation The high prevalence of sleep-disordered breathing recorded in our population-based sample might be attributable to the increased sensitivity of current recording techniques and scoring criteria. These results suggest that sleep-disordered breathing is highly prevalent, with important public health outcomes, and that the definition of the disorder should be revised. Funding Faculty of Biology and Medicine of Lausanne, Lausanne University Hospital, Swiss National Science Foundation, Leenaards Foundation, GlaxoSmithKline, Ligue Pulmonaire Vaudoise.